Tillaux Fracture In Adult: A Case Report - Syed T; Storey P; Rocha R; Kocheta A; Singhai S (Orthopaedic Journal of M. P. Chapter, 2020)
We report a rare case of Tillaux fracture of the ankle in a 36-year-old man. He sustained the injury in a football tackle and presented to us with pain and swelling of the left ankle. After preliminary X-rays, a CT scan was done which showed a Tillaux type fracture which is a rare injury after epiphyseal fusion. The ankle was treated with open reduction and internal fixation with screws and plaster for 6 weeks. At 3 months the patient had no pain in the ankle and able to mobilize full weight bearing on that side.